Performance of Silica Membranes from Fly Ash Coal of PT Semen Baturaja in Reducing Metal Content in Mine Acid Water - Lety Trisnaliani; Indah Purnamasari; Fatria Ahmadan (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Mine acid water has a high level of acidity as a result of oxidation of rocks containing pyrite and sulfide minerals from the remains of rocks exposed to oxygen in the water, which usually contain high metal content. One way to reduce the metal content in acid mine water is to use a silica membrane. In the study, silica membranes were made by extracting silica from fly ash by using two types of solvents or extractors, namely HCl and HNO3. The adsorption time are 100 minutes, 120 minutes, and 140 minutes with the aim to find out which extractors can produce membranes with performance good and optimum time in the absorption of metal content from acid mine drainage. SEM analysis shows that there is no pore formed on the membrane. Based on the results of the analysis of the research conducted, it can be seen that the membrane with HCl extractor can work better in reducing metal content with optimum adsorption time in the 140th minute. Acid mine drainage also experienced a decrease in flux from 14.9283 L / m2 hours to 6.8244 L / m2h for the membrane with HCl extractor and for HNO3 membrane decreased from 11.9427 L / m2h to 7.6774 L / m2h. Keywords: Silica Membranes, Fly Ash Coal, Metal Content, Mine Acid Water, extractor